2021
DOI: 10.1111/avj.13123
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with small lungworm infections in heavily infected sheep in southeast South Australia

Abstract: This field observational study describes the seasonal pattern of small lungworm infections under different grazing managements from August 2018 to March 2019. Live weight, lungworm and gastrointestinal nematode infection, as well as pasture type grazed and snail density, were measured at 5 farm visits. Across all visits and mobs, about one quarter to one half of sheep were positive for small lungworm, although prevalence was as low as 0% and as high as 78%. The density of the intermediate host molluscs was gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The greater susceptibility of goats to nematode infection, both gastrointestinal and pulmonary, may be related to the low ability to develop a specific protective immune response. It has been suggested that the type of grazing (in height) may have contributed to this evolutionary specificity of the immune response against nematode parasites [31,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater susceptibility of goats to nematode infection, both gastrointestinal and pulmonary, may be related to the low ability to develop a specific protective immune response. It has been suggested that the type of grazing (in height) may have contributed to this evolutionary specificity of the immune response against nematode parasites [31,62].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being non-invasive, simple, and inexpensive, the Baermann technique has suboptimal sensitivity. Indeed, sensitivity of the Baermann technique did not exceed 80% for M. capillaris in sheep using pooled samples [17,18].…”
Section: Introductionmentioning
confidence: 94%